PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VD SD NEGERI 184 PEKANBARU - Salti, Devi Leri Yudha; ', Erlisnawati; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to increase the student’s mathematic outcomes at fifth grade in SDN 184 Pekanbaru by using cooperative learning model type Numbered Heads Together (NHT). Problems in SDN 184 Pekanbaru are 1) Students are less able to understand the matter presented teacher, 2) the student are less active when learning process, 3) Smart student don’t want to help students weak in the learning process, especially in group discussion activities. The subject in this research are fifth that totally is 30 who is 8 male students and 22 female students. Object in the research is to increase the student’s mathematic outcomes by using cooperative learning model type Numbered Heads Together (NHT) at fifth grade in SDN 184 Pekanbaru. This research is two cycles, the each cycle consisting of two meetings and test. The average percentage of the students is 70% in the first cycle and increase 83.3% in the second cycle, before using the model is 53.3%,. The average student’s learning outcomes increase from base score to first cycle is 9.1% , the second cycle average student’s learning outcomes is 16.7%. Basically the student’s learning outcomes can be show of cooperative learning model type Numbered Heads Together (NHT) can to increase the student’s mathematic outcomes at fifth grade in SDN 184 Pekanbaru.Keywords: Cooperative Learning Model Type Numbered Heads Together (NHT), Mathematic Learning Outcomes2